Support for families intellectually disabled child by the Centers for Rehabilitation - Education - Educational in the Silesian Agglomeration - Tomkiewicz-Montowska, Laura (Journal of Education, Health and Sport, 2018)
Introduction: A child with intellectual disability and take care of him is a big challenge for the whole family. There is no doubt, that parents need support for themselves and their children in order to cope with numerous burdens. The article deals with the problem of supporting families of a child with intellectual disabilities according the Centers of Rehabilitation and Education in the Silesian Agglomeration. This study is an attemptation to identify the role of parents in the process of care and education of a child with intellectual disability, furthermore a family support system too. Objectives: The aim of the study is to describe and identify the assistance of family with the intellectually disabled child according the support of Centers of Rehabilitation and Education in the Silesian Agglomeration. Material and methods: In the research, the questionnaire survey was carried out among the Centers of Rehabilitation and Education in Chorzów and Bytom cities, from March to April 2014. The MS Excel application and the SPSS program were used to set up the database and statistical analysis of the collected informations. Further, the contingency tables were performed. By using the chi-square independence test (χ2 test), the relationship between variables was checked. It was assumed that the results are statistically significant at p ≤ 0.05. Results: Among the surveyed parents, more than 63% admitt that they are looking for support in understanding and accepting the disability of their child. Every eighth family sought help among the Association’s centers. Each supported family by the OREW Association have a certain expectations to them. The research find out, that every fourth respondent (23.9%) expect much more rehabilitation and education. On the second place is to improve the child’s health. The 17.4% of respondents assessed that their expectations are fulfilled. Findings of the surveyed employees of Centers of Rehabilitation and Education shows that, more than 40% do not appreciate the cooperation with parents and guardians of disabled childs. In addition, every third respondent do not answer to this question. Every fourth employee believes that parents and attendant have insufficient knowledge about the disability of their own child. Conclusions: Undoubtedly, the activity of Centers of Rehabilitation and Education is invaluable. It is necessary to increase and tightening the cooperation of parents and guardians of disabled child with employees of Centers of Rehabilitation and Education like OREW Institutions. Shared work on the development of children and mutual support will certainly contribute to commensurate results. The presence and attitude of parents directly promote the progress of their disabled child.